2021
DOI: 10.17275/per.21.65.8.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Peer and Self-Assessment-Based Editorial Study on Students’ Ability to Follow Spelling Rules and Use Punctuation Marks Correctly

Abstract: skills are defined as an individual's efficacy in self-expression, ability to communicate in social life, and capacity for academic success at a later age (Tavşanlı, 2019). In addition, it is known that cognitive development, creative and critical thinking, research and problem solving skills, phonological awareness, recognition of words, reading comprehension, and using language operate at a higher level in individuals that have good writing skills (Aram 2005; Bloodgood, 1999; Shatil, Share & Levin, 2000). Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…The results yield no significant difference between the experimental groups. This finding is in tune with the Elola and Oskoz's (2010) study in terms of overall improvement and with Tavşanlı and Kara's (2021) study in terms of spelling and grammar improvements.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results yield no significant difference between the experimental groups. This finding is in tune with the Elola and Oskoz's (2010) study in terms of overall improvement and with Tavşanlı and Kara's (2021) study in terms of spelling and grammar improvements.…”
Section: Discussionsupporting
confidence: 85%
“…These results can be attributed to the help of the software. These results are supported by different studies such as Wang and Wang's (2012), Wang et al's (2013), Li and Hegelheimer's (2013), and Tavşanlı and Kara's (2021). These studies found improvement in the post-test scores for both the automated editing.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The experimental data showed an incredibly easy contingency contracting intervention to aid students who have difficulty writing while producing a text to enhance punctuation performance. Another study found that using spelling standards and punctuation correctly can be improved by using Peer and Self-Assessment-Based Editorial studies (Tavşanli & Kara, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Errors in the written text are likely to lead them to form a negative impression. When researchers examine writing skills, as a rule, they consider and evaluate them as a complex phenomenon (Graham & Harris, 2011;Hardman & Bell, 2019), and few studies are devoted separately to the spelling rules and to the use of punctuation marks (Al-Tamimi, 2018;Ali et al, 2020;Tavşanlı & Kara, 2021).…”
Section: Introductionmentioning
confidence: 99%